Crisis y muerte en la Antigüedad : reflexiones desde la historia y la arqueología - Martínez García, José Javier,; Conesa Navarro, Pedro David, (Access archaeology., 2022)
This text takes a multidisciplinary and international perspective to analyse periods of crisis in the Ancient World from a historical and archaeological point of view. To this end, the contributors have focused on periods of health and environmental crises, as well as persecutions and periods of famine and starvation during antiquity.